An Optimal Sink Nodes Number Estimation for Improving the Energetic Efficiency in Wireless Sensor Networks - Staniec, K.; Debita, G. (Elektronika ir Elektrotechnika, 2013)
The paper is dedicated to the issue of reducing the energetic consumption by nodes of a wireless sensor network, by means of deliberately choosing an optimal number of sink nodes in the network. It is shown that an optimal choice of the sink may halve the total number of hops needed for the information from each node to reach it, relative to the sink of the worst choice. Similar research performed on networks with multiple sinks has led to the formulation of a concise formula which allows calculating an optimal number of sinks in an N-populated WSN such that a trade-off is met between the energetic and economical savings. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5407